The impact of economic crisis on Greek regions and the importance of regional resilience - Stella Karoulia; Eleni Gaki (European Regional Science Association (ERSA), 2013)
The global economic crisis of 2008 has affected all European countries; Greece of course could not be the exception to this "rule". First, the fact that Greece was unable to mitigate its public expenditures and to increase its revenues in comparison with the other European countries and other the weaknesses of the Economic and Monetary Union (EMU) design which led to a structural asymmetry within the Eurozone, contributed to Greece's "acquaintance" with the economic crisis. Its impact on Greek regions has become more intense during the last three years. Taking into consideration some indicators which are directly affiliated with the economic and social welfare, for example GDP, disposal income, employment/unemployment, population, infant mortality, proportion of pupils etc, before and after the crisis it is easily ascertained that the Greek regions are moved to unprecedented high rates of under-development. For instance, the most developed Greek region, Attica, which hadn't experienced before high rates of unemployment, now it is in the same class with regions that had traditionally high rates of unemployment. The goal of this paper is to examine the extent to which each region has been hit by the economic crisis -because each of them has been affected to different degree- using certain indicators which are presented minutely in the research. We do not focus our attention on some specific regions; instead of this we examine all regions whether they are developed or under-developed. Moreover, throughout this research we also pursue to investigate the regional disparities which induce to the differential impact of the crisis and which worsened due to the austerity measures that were applied. Regional disparities reflect permanent structural or macroeconomic imbalances in the production model of the country and the causes of their existence are geographical and environmental factors, the regions' social structure, the low mobility of labor and capital, institutional and political factors and external economies. Furthermore, this paper investigates the degree of resilience of each region during the crisis i.e. whether they can cope with it, overcome it and recover from it. In order to ascertain it we will examine if regions dispose resourcefulness, performance, redundancy, diversity, innovative learning, connectedness, robustness and rapidity. Finally, we will valuate the regional resilience and we will examine whether it is resistance, recovery, re-orientation or renewal (or resumption).
Keywords: 330; Economic crisis; Greece; Regional disparities; Regional resilience